2015
DOI: 10.1103/physrevb.91.020409
|View full text |Cite
|
Sign up to set email alerts
|

Pressure dependence of the magnetic order in CrAs: A neutron diffraction investigation

Abstract: The suppression of magnetic order with pressure concomitant with the appearance of pressureinduced superconductivity was recently discovered in CrAs. Here we present a neutron diffraction study of the pressure evolution of the helimagnetic ground-state towards and in the vicinity of the superconducting phase. Neutron diffraction on polycrystalline CrAs was employed from zero pressure to 0.65 GPa and at various temperatures. The helimagnetic long-range order is sustained under pressure and the magnetic propagat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 16 publications
4
48
0
3
Order By: Relevance
“…At ambient pressure CrAs is characterized by a relatively high Néel temperature T N 270 K [65][66][67][68]. T N decreases approximately by a factor of three for pressures (p) approaching 0.7 GPa, above which the magnetism completely disappears [65,66].…”
Section: Pressure-induced Electronic Phase Separation Of Magnetism Anmentioning
confidence: 99%
“…At ambient pressure CrAs is characterized by a relatively high Néel temperature T N 270 K [65][66][67][68]. T N decreases approximately by a factor of three for pressures (p) approaching 0.7 GPa, above which the magnetism completely disappears [65,66].…”
Section: Pressure-induced Electronic Phase Separation Of Magnetism Anmentioning
confidence: 99%
“…By increasing the pressure, the lattice parameters a and c both show a non-monotonic change whereas the lattice parameter b undergoes a rapid contraction at ∼0.18-0.35 GPa, which suggests a pressure-induced isostructural phase transition. 15,20 The T c vs P phase diagram of CrAs resembles that of many of the unconventional superconducting systems above mentioned suggesting the presence of strong antiferromagnetic fluctuations near the critical pressure P c and a possible uncon-Typeset by REVT E X arXiv:1709.07481v1 [cond-mat.str-el] 21 Sep 2017 ventional pairing mechanism. 15 For the sake of completeness we mention that detailed studies of the stability of the ferromagnetism in CrAs crystallizing in the zinc-blende structure have been reported.…”
Section: Introductionmentioning
confidence: 97%
“…The helimagnetic phase is suppressed at about 0.7 GPa, and the superconductivity is realized in a wide pressure range, in the non magnetic state, with a maximum T c ∼ 2.2 K at 1.0 GPa. [17][18][19][20] The structure of CrAs remains stable up to 1.8 GPa, whereas the lattice parameters exhibit anomalous compression behaviors. By increasing the pressure, the lattice parameters a and c both show a non-monotonic change whereas the lattice parameter b undergoes a rapid contraction at ∼0.18-0.35 GPa, which suggests a pressure-induced isostructural phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…The pressure-related structural changes occurred concurrently with the appearance of bulk superconductivity, shedding light on the structural and related electronic responses to high pressure, which play a key role toward understanding the superconductivity of CrAs. also been investigated by Keller et al (18), where T N was observed to decrease with increasing pressure (18,19). Measurement of the electrical conductivity of CrAs at 4.2−350 K under high pressure up to 0.9 GPa was performed by Zavadskii and Sibarova (20).…”
Section: Significancementioning
confidence: 99%